Metrological intercomparison of six terrestrial laser scanning systems. Issue 2 (1st March 2018) - González‐Jorge, Higinio; Rodríguez‐Gonzálvez, Pablo; Shen, Yueqian; Lagüela, Susana; Díaz‐Vilariño, Lucía; Lindenbergh, Roderik; González‐Aguilera, Diego; Arias, Pedro
Abstract : Intercomparison among six terrestrial laser scanner systems focused on the measurement of small elements ( < 0.5 m) is performed. Phase shift (PS) and time of flight (ToF) scanners are considered. Two standard artefacts containing three‐dimensional printing spheres and steps of variable height are used for the experiment. Results show errors between −4.5 and 3.5 mm in the measurement of distances between step planes. The most stable systems for measuring small elements seem the Leica C10, Faro Photon and Riegl LMS Z390i. The quality of the results is linked to the overall quality of the system rather than the specific technology used for range measurement (PS or ToF) which does not appear to be a determining factor.